Assessment of left ventricle systolic and diastolic functions in schizophrenia patients - Korkmaz, Sevda; Korkmaz, Hasan; Ozer, Omer; Atmaca, Murad (Elsevier Ireland Ltd, 2016)
The objective of the study was to scrutinize in detail the changes that occur in left ventricle (LV) systolic and diastolic functions using echocardiography in patients with at least 5 years of history and 40 healthy volunteers matching the patients in age and gender, who were enrolled in a cross-sectional study. All cases were examined with Tei Index, an index that could assess LV systolic and diastolic functions in conjuction, and with LV ejection fraction (LVEF) that assesses systolic function. In addition, Mitral E and A wave velocities, Isovolemic relaxation time (IVRT), Tissue Doppler Em (peak early motion) and Am (peak after motion) waves, which evaluate diastolic functions were measured. Tei Index was calculated as 0.61 +/- 0.19 in the patient group, and as 0.39 +/- 0.10 in the control group and the difference was statistically significant (p < 0.001). LVEF was measured as 58% +/- 5 in the patient group, and as 62% +/- 3 in the control group and the difference was statistically significant (p < 0.001). Also the IVRT values were significantly different between the tissue Doppler Em and Em/Am ratio among the groups (p < 0.001). Echocardiographic myocardial performance, LV systolic and diastolic functions in schizophrenia patients was found to be worse than those of the control group. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Schizophrenia; Myocardial performance; Diastolic dysfunction; Systolic dysfunction